Genomic characterization of two carbapenem-resistant Serratia marcescens isolates causing bacteremia: Emergence of KPC-2-encoding IncR plasmids - Jia, Junli; Huang, Lisha; Zhang, Long; Sheng, Yanbing; Chu, Weili; Xu, Hao; Xu, Aiguo (Frontiers in Cellular and Infection Microbiology, 2023)
The occurrence and transmission of carbapenemase-producing-Enterobacterales (CPE) on a global scale has become a major issue. Clinical reports are rarely providing information on the genomic and plasmid features of carbapenem-resistant Serratia marcescens. Our objective was to investigate the resistance and transmission dynamics of two carbapenem-resistant S. marcescens that are resistant to carbapenem and have caused bacteremia in China. Blood specimens were taken from two individuals with bacteremia. Multiplex PCR was employed to identify genes that code for carbapenemase. Antimicrobial susceptibility tests and plasmid analysis were conducted on S. marcescens isolates SM768 and SM4145. The genome of SM768 and SM4145 were completely sequenced using NovaSeq 6000-PE150 and PacBio RS II platforms. Antimicrobial resistance genes (ARGs) were predicted using the ResFinder tool. S1 nuclease pulsed-field gel electrophoresis (S1-PFGE) and southern blotting were employed to analyze plasmids. Two S. marcescens that produced KPC-2 were identified from bloodstream infections. The antimicrobial susceptibility testing demonstrated that both of the isolates had a resistance to various antibiotics. The whole-genome sequence (WGS) and plasmid analysis revealed the presence of blaKPC-2-bearing IncR plasmids and multiple plasmid-borne antimicrobial resistance genes in the isolates. Our comparative plasmid analysis suggested that the two IncR plasmids identified in this study could be derived from a common ancestor. Our findings revealed the emergence of blaKPC-2-bearing IncR plasmid in China, which could be a hindrance to the transmission of KPC-2-producing S. marcescens in clinical settings.